THE DEVELOPMENT OF TEACHING LEARNING MATERIALS MATHEMATICS WITH SCIENTIFIC APPROACH BASED ON PROBLEM BASED LEARNING TO LEARN CIRCLE FOR JUNIOR HIGH SCHOOL STUDENTS GRADE VIII - Rydlo Ega Putra; Marsigit . (Jurnal Pedagogi Matematika, 2017)
The aims of this research was to produce teaching learning materials such as lesson plan and worksheet with scientific approach based on problem based learning method to learn circle for junior high school studentsgrade VIII. The quality of teaching learning materials that was developed observation in terms of three aspect of quality these were validity, practicality, and effectiveness. The method used was the Research and Development (RD) with  ADDIE  model  that  includes  analysis,  design,  development,  implementation,  and  evaluation.  This research was produced teaching learning materials such as lesson plan and worksheet. The validity score of the lesson  plan  was 4,10 with  valid  classification.  While  the validity score of  worksheet was 4,06 with  very  valid classification. The result of the questionnaire from teacher and student showed that the teaching learning materialswas  practical  with  total  score  4,08.  The  result  of  observervation  during  the  learning  process  showed  good classification  with  percentage  up  to  89%.  The  result  of  student  competency  showed  that teaching  learning materials was very effective with percentage 85,71%.